Molecular insights and diagnostic advances in strawberry-infecting viruses - Bo Yan; Mengjiao Lu; Jijing Han; Yuhao Cao; Fei Yan; Xuemei Song (Frontiers in Microbiology)
Strawberry (Fragaria × ananassa Duch.) production is threatened by more than 20 viral pathogens, which frequently occur in mixed infections, leading to significant yield losses and diagnostic complexities. This review summarizes recent advances in the biology and molecular biology of the major strawberry-infecting viruses, strawberry vein banding virus, strawberry necrotic shock virus, strawberry mottle virus, strawberry latent ringspot virus, strawberry mild yellow edge virus, strawberry pallidosis-associated virus, and strawberry polerovirus 1. It reviews the molecular interactions between viruses and strawberry and also highlights cutting-edge detection technologies, including high-throughput sequencing, RT-PCR/qPCR, and isothermal amplification coupled with lateral flow assays. Despite these advances, critical research gaps remain, particularly in the functional characterization of viral proteins, the mechanisms underlying synergistic and antagonistic interactions in mixed infections, and the development of rapid, field-deployable diagnostic tools. Addressing these challenges is essential for enhancing virus-free certification programs, guiding targeted breeding efforts, and implementing effective disease management strategies to ensure the sustainability of global strawberry production.